Characteristics of Fasting in Ramadan in Type 2 Diabetes Patients on Empagliflozin in the DAR Global Surveys of 2020 and 2022 - Hassanein, Mohamed; Hafidh, Khadija; Shaikh, Shehla; Shaltout, Inass; Malek, Rachid; Hussein, Zanariah; Alamoudi, Reem; Ahmedani, Muhammad Yakoob (Journal of Diabetes and Endocrine Practice, 2025)
The safety of Ramadan fasting in individuals is determined by an interplay between Ramadan, patients, and medication factors.To analyze the challenges associated with Ramadan fasting among patients with diabetes treated with Empagliflozin and other antiglycemic agents who participated in the Diabetes and Ramadan (DAR) global surveys of 2020 and 2022.Building on data from the DAR Global surveys, a sub-analysis was performed on patients treated with Empagliflozin (n = 1,464) to reflect on the patients' experience and to analyze the challenges associated with Ramadan fasting.The observational survey was conducted in five geographic regions (Gulf countries, Maghreb countries, Middle East [Egypt, Türkiye, and Iraq], Indian subcontinent, and Southeast Asia) in Muslim type 2 diabetes patients post-Ramadan 2020 and 2022. The patients were divided into four groups: Those treated with (1) Empagliflozin without sulphonylureas or insulins, (2) Empagliflozin plus sulphonylureas, (3) Empagliflozin plus insulins, and (4) Empagliflozin plus sulphonylureas and insulins. Descriptive statistics on medical data and baseline demographics were generated, and odds ratios regarding symptomatic hyper- and hypoglycemic events were calculated. The fasting behavior as well as diabetes management of the patients were evaluated.Despite having diabetes, a large proportion of patients fasted during Ramadan. Patients treated with Empagliflozin without sulphonylureas or insulins showed significantly lower symptomatic hypo- and hyperglycemic complication rates during Ramadan fasting (6.9 and 8.4%, respectively). In patients on concomitant treatment with sulphonylureas, slightly higher rates of symptomatic hyper- and hypoglycemic events were observed. In patients who received insulins, significantly higher rates of symptomatic hyper- and hypoglycemic events were observed. The highest rates of symptomatic hypo- and hyperglycemic events (19.7 and 22.2%, respectively) were observed in patients who were given concomitant treatment with sulphonylureas and insulins, with odds ratios up to 3.31 compared to Empagliflozin without sulphonylureas or insulins. Very low hospitalization rates (0.38%) due to symptomatic hyper- and hypoglycemic events were observed.Hypoglycemia rates were influenced by the type of therapies administered to the patients. Based on the results of this study, it may be concluded that Empagliflozin monotherapy or in combination with sulphonylureas may be relatively safe for Ramadan fasting, whereas caution is advised for patients taking additional insulin combinations.
Keywords: Ramadan; fasting; type 2 diabetes; Empagliflozin; hypoglycemia; hyperglycemia